Soroprevalência da infecção pelo vírus da hepatite B e C em pacientes com doença renal crônica em diálise em centro de referência estadual, Belém, Pará, Brasil - MIRANDA, José Vitor da Silva (2023)
INTRODUCTION: Hepatitis B (HBV) and C (HCV) are responsible for the vast majority of parenteral viral hepatitis infections in humans, with a higher prevalence of HBV and HCV in patients with end-stage renal disease on hemodialysis (HD). The Amazon region has high notification of cases of infection by the HBV and HCV viruses, and in Brazil the prevalence of HCV in hemodialysis patients is three times higher than that reported for the general Brazilian population. OBJECTIVES: This study aims to analyze the sociodemographic and clinical profile of the population undergoing hemodialysis in a hemodialysis center of a tertiary hospital in the Amazon region, in addition to studying the seroprevalence of HBV and HCV infection in this region, and inferring whether there is a correlation between the levels of Anti-Hbs, Anti-Hbc total, Anti-HCV and the diagnosis of HBV with the duration of hemodialysis, as well as gender, age group, schooling, period of hemodialysis, and blood transfusions. METHODS: This is a crosssectional study of prevalence, which will use the registration and systematic observation of medical records and screening of these infections in patients in the dialysis program. RESULTS: Of the 116 patients studied, 60.34% were male, 32.76% belonged to the age group: 48 62 years (32.76%). Regarding the clinical profile: 55.17% of the patients have been on HD for < 60 months. Laboratory data: seroprevalence for positive Anti-Hbs (75%), total nonreactive Anti-Hbc (83.04%), non-reactive HBsAg (100%). Association between serological diagnosis of HBV and hemodialysis time > 60 months. (OR 7.94, 95% CI 2.12 - 29.83). CONCLUSION: Patients with more than 60 months of hemodialysis (HD) are more likely to be diagnosed as: previous contact with wild hepatitis B virus. There is a possible association between exposure (HD) and outcome (contact with wild virus). There was no statistical association of dependence between the group (HD time > 60 months) and positive serology for HCV. There was a higher frequency of positive Anti-Hbs, nonreactive total Anti-Hbc, and the seroprevalence of positive HbsAg was null, and of positive Anti-HCV was less than 5%.